Disclosing A Side of Internal Submission Control and Payment of Claims: Study of Ethnomethodology on the BPJS in Yogyakarta - Mega Harum Ramadhani; Robiatul Auliyah; Muhammad Asim Asyari (Faculty of Economics, Universitas Sriwijaya, 2017)
The purpose of the research is conducted to know the implementation of internal control on the process of submission and payment of claims by BPJS Kesehatan Yogyakarta. As well as knowing the process of submission and payment of claims. This type of research is qualitative research using ethnomethodology approach. Researchers use ethnomethodology method as the basis to expose the daily activities of the process of submission and payment of claims. Technique of Data collection through interviews with relevant informants and make direct observation to the object of research. The results of this research are to answer the problem and the purpose of this research, that BPJS Kesehatan has implemented internal control with maximum. Internal controls are capable to detect red flags in the submission process and payment of claims. Although there are some